Investigating the embodied energy and carbon of buildings: A systematic literature review and meta-analysis of life cycle assessments - Minunno, Roberto; O'Grady, T.; Morrison, Greg; Gruner, R.L. (PERGAMON-ELSEVIER SCIENCE LTD, 2021)
Life cycle assessment is a tool to quantify the environmental impact of products and has been widely studied in the building context. This is an important context given the building sector's substantial embodied energy and carbon. Against this backdrop, this study has two main objectives. The first objective is to create a benchmark the environmental impact of buildings. The second objective is to develop a procedural guideline that assists practitioners in decreasing the environmental impact of buildings. To achieve these objectives, a systematic review of the relevant literature was conducted to categorize and summarize relevant studies. A meta-analysis followed to synthesize the life cycle assessment results that emerged from the collected articles. The articles were categorized into two main groups: articles on construction materials and articles on entire buildings. Eight construction materials (i.e., concrete, reinforcement bars, structural steel, timber, tiles, insulation, and plaster) and three building types (i.e., concrete, timber, and steel) were identified, and related embodied energy and carbon were extracted. Subsequently, the data were analyzed through descriptive and inferential statistics. Findings from the meta-analysis informed a regression model, which in turn informed a procedural guideline for practitioners who seek to reduce buildings' environmental impact. Further, the findings of this paper shed light on previously equivocal results concerning the impact of construction materials and buildings, but also support previous findings for structural materials, showing, for example, that the use of timber structures results in substantial savings over concrete structures in terms of both embodied energy (43%) and carbon (68%).